2012
DOI: 10.1039/c2cp40187h
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic energy transport along PEG chains: distance dependence of the transport efficiency

Abstract: Dual-frequency relaxation-assisted two-dimensional infrared (RA 2DIR) spectroscopy was used to investigate energy transport in polyethylene glycol (PEG) oligomers of different length, having 0, 4, 8, and 12 repeating units and end-labeled with azido and succinimide ester moieties (azPEGn). The energy transport initiated by excitation of the N≡N stretching mode of the azido group in azPEGn in CCl(4) at ca. 2100 cm(-1) was recorded by probing the C=O stretching modes (reporters) of the succinimide ester moiety. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
64
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(72 citation statements)
references
References 51 publications
8
64
0
Order By: Relevance
“…It has been established that in polyatomic molecules the vibrational excitation is not evenly distributed among a large number of intramolecular vibrations, but it is transferred, for example, through a chain consisting of 12-26 CH 2 units [21,22] and between moieties linked by 4-8 conjugated bonds [23]. Using the method of the two-dimensional (2D) infrared spectroscopy [23], Lin et al have shown that transport of the intramolecular vibration energy in the polyethylene glycol (PEG) oligomers of different length, having 4, 8, and 12 repeating units [24], and in perfluoroalkane oligomers with various chain lengths [25] occurs in a ballistic energy transport regime. In the ballistic regime the energy is transferred by vibrational states delocalized over the whole transport region [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been established that in polyatomic molecules the vibrational excitation is not evenly distributed among a large number of intramolecular vibrations, but it is transferred, for example, through a chain consisting of 12-26 CH 2 units [21,22] and between moieties linked by 4-8 conjugated bonds [23]. Using the method of the two-dimensional (2D) infrared spectroscopy [23], Lin et al have shown that transport of the intramolecular vibration energy in the polyethylene glycol (PEG) oligomers of different length, having 4, 8, and 12 repeating units [24], and in perfluoroalkane oligomers with various chain lengths [25] occurs in a ballistic energy transport regime. In the ballistic regime the energy is transferred by vibrational states delocalized over the whole transport region [24].…”
Section: Introductionmentioning
confidence: 99%
“…Using the method of the two-dimensional (2D) infrared spectroscopy [23], Lin et al have shown that transport of the intramolecular vibration energy in the polyethylene glycol (PEG) oligomers of different length, having 4, 8, and 12 repeating units [24], and in perfluoroalkane oligomers with various chain lengths [25] occurs in a ballistic energy transport regime. In the ballistic regime the energy is transferred by vibrational states delocalized over the whole transport region [24]. The energy transport speed was found to be 450 m/s for the PEG oligomers in CCl 4 [24] and 1150 m/s for perfluoroalkane oligomers in chloroform [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are close to a speed of propagation (950 m/s) of the heat burst in a monolayer of longchain hydrocarbon molecules anchored to metal substrates that was measured by using the method of the sum-frequency generation spectroscopy [23]. It has been found that the vibrational energy transport time increases with increasing the chain length and reaches about 15 ps at the chain length of 6 nm [26].…”
Section: Description Of the Modelmentioning
confidence: 95%
“…Using the method of the twodimensional infrared spectroscopy [25], Rubtsov and co-workers have shown that transport of the intramolecular vibration energy in the polyethylene glycol (PEG) oligomers of different lengths [26] and in perfluoroalkane oligomers with various chain lengths [27] occurs in a ballistic energy transport regime, in which the energy is transferred by vibrational states delocalized over the whole transport region [26]. The energy transport speed was found to be 450 m/s for the PEG oligomers in CCl 4 [26] and 1150 m/s for perfluoroalkane oligomers in chloroform [27]. These values are close to a speed of propagation (950 m/s) of the heat burst in a monolayer of longchain hydrocarbon molecules anchored to metal substrates that was measured by using the method of the sum-frequency generation spectroscopy [23].…”
Section: Description Of the Modelmentioning
confidence: 99%